Pendidikan Berbasis Ayat Hadits: Membangun Generasi Berkualitas dalam Era Digital - Iffiani, Zelly; Mahmudi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Education is the main foundation in forming a superior generation, especially in the digital era which is full of dynamics and rapid change. This article discusses the concept of verse and hadith-based education as an effort to build a quality generation in the context of modern technology. The integration of Islamic values, which originate from verses and hadith, is the main foundation in shaping the character, morality and adaptability of the younger generation. This article highlights the long-term benefits of such education, including establishing a balance between technology and spirituality, the ability to face the challenges of the digital era, preventing the negative impacts of technology, and empowering generations to make positive contributions to society. With a holistic approach, it is hoped that education based on hadith verses can create a generation that is not only intellectually intelligent but also has high moral and spiritual sensitivity, so that it is able to make a positive contribution in facing the complexities of the digital era. This writing uses a qualitative method with a descriptive approach through literature studies and several scientific sources related to Islam and technology. The results explain the importance of the family's role in educating their children. Education in the family must be future-oriented, meaning that the education given by parents to their children is more about practical preparation so that children can face the times they will experience in the future. Moreover, digital technology brings long distances closer together. Providing possibilities for children's progress in learning digital technology by always measuring through artificial intelligence digital applications.